Державний суверенітет і територіальна цілісність – фундаментальні національні інтереси України - Носач, А. В.; Nosach, A. V. (Науковий вісник Дніпропетровського державного університету внутрішніх справ. – 2019. – № 3. – С. 244-249, 2019)
У межах наукової статті розкрито зміст та сутність понять «державний суверенітет» і «територіальна цілісність». Досліджено проблему, визначення змісту фундаментальних національних інтересів України та співвідношення з ними таких понять, як державний суверенітет і територіальна цілісність України. Наголошено на тому, що посягання на державний суверенітет і територіальну цілісність України як на сферу національних інтересів держави визнаються характерними ознаками злочинності.

The research is aimed to analyze state sovereignty and territorial integrity as the fundamental national interests of Ukraine and to identify them as a characteristic feature of crime in this area. To achieve the scientific goal set forth, the content is revealed and an analysis of certain scientific aspects is carried out. First, the content and essence of the concepts of «state sovereignty» and «territorial integrity» are clarified. Secondly, an understanding of national interests and relations with them of state sovereignty and territorial integrity of Ukraine are provided. Thirdly, the state sovereignty and territorial integrity of Ukraine are considered as a characteristic feature of crime in this area. State sovereignty is the supremacy of state power within the country and its independence and equality in the foreign policy sphere. The main content and essence of state sovereignty is revealed through the prism of the analysis of its legally significant features, namely: unity, supremacy and independence of state power. Territorial integrity is an inalienable right of Ukraine, which consists in the inviolability of its territory within its borders and the prohibition of anyone to make a decision, and, with it, to implement it, to change this territory without the consent of Ukraine itself. The term «national interest» refers to the vital interests of man, society and the state, the realization of which is ensured by the state sovereignty of Ukraine, its progressive democratic development, as well as safe living conditions and welfare of its citizens. In accordance with the provisions of the Law on National Security to the fundamental national interests of Ukraine belongs state sovereignty and territorial integrity. Summing up, the following is emphasized: - state sovereignty and territorial integrity act as the fundamental national interests of Ukraine; - state sovereignty of Ukraine is understood as the power of the state within its territory; - the territorial integrity of Ukraine is the inviolability of its territory within its borders and the prohibition of its change by anyone without the consent of Ukraine; - state sovereignty and territorial integrity of Ukraine are defined as one of the characteristic features that form the content of crimes against the state sovereignty and territorial integrity of Ukraine.

Раскрыто содержание и сущность понятий «государственный суверенитет» и «территориальная целостность». Исследована проблема, определения содержания фундаментальных национальных интересов Украины и соотношение с ними таких понятий, как государственный суверенитет и территориальная целостность Украины. Отмечено, что посягательство на государственный суверенитет и территориальную целостность Украины как на сферу национальных интересов государства признаются характерными признаками преступности.
Носач А. В. Державний суверенітет і територіальна цілісність – фундаментальні національні інтереси України / Носач А. В. // Науковий вісник Дніпропетровського державного університету внутрішніх справ. – 2019. – № 3. – С. 244-249.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; державний суверенітет; територіальна цілісність; національні інтереси; фундаментальні національні інтереси України; злочини проти державного суверенітету і територіальної цілісності; государственный суверенитет; территориальная целостность; национальные интересы; фундаментальные национальные интересы Украины; преступления против государственного суверенитета и территориальной целостности; state sovereignty; territorial integrity; national interests; fundamental national interests of Ukraine; crimes against state sovereignty and territorial integrity